2007
DOI: 10.1111/j.1365-2141.2007.06916.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of dose requirements for sustained in vivo activity of a therapeutic human anti‐CD20 antibody

Abstract: SummaryWe evaluated the dose requirements for sustained in vivo activity of ofatumumab, a human anti‐CD20 antibody under development for the treatment of B cell‐mediated diseases. In a mouse xenograft model, a single dose, resulting in an initial plasma antibody concentration of 5 μg/ml, which was expected to result in full target saturation, effectively inhibited human B‐cell tumour development. Tumour growth resumed when plasma concentrations dropped below levels that are expected to result in half‐maximal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 24 publications
5
65
0
Order By: Relevance
“…23,24 Therefore, understanding the exposureresponse relationship for drug candidates in a preclinical model could aid in predicting the optimal dose and regimen in patients. 25 For example, the active plasma concentration of cetuximab in a mouse xenograft model was fairly comparable with those observed in patients. 26 A mechanism-based model could add additional values for translational purpose.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…23,24 Therefore, understanding the exposureresponse relationship for drug candidates in a preclinical model could aid in predicting the optimal dose and regimen in patients. 25 For example, the active plasma concentration of cetuximab in a mouse xenograft model was fairly comparable with those observed in patients. 26 A mechanism-based model could add additional values for translational purpose.…”
Section: Discussionmentioning
confidence: 60%
“…However, there are some wellknown challenges in predicting the clinical efficacious dose based on preclinical data. 25 Saturating targets allows for plasma and tumor concentrations to remain within the linear range; however this is only desirable if target saturation is linked to efficacy. Thus, it is important to take into account other factors, such as dose, patient variability, antigen density/turnover, tumor burden, and/or degree of tumor perfusion in order to provide an exposure margin for efficacy in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…In cynomolgus monkeys, a 1.25 mg/kg intravenous (IV) dose administered daily for four days effectively depleted B-cells; initial plasma concentrations were approximately 50 μg/mL. 17 The cell count did not return to a normal level until 96 days later, but the animals developed primate antihuman antibodies (PAHA). Taken together, the results from the mouse and monkey experiments suggested that high initial dosing would be necessary to saturate CD20, but maintenance at 5-10 μg/mL would likely be sufficient for prolonged activity.…”
Section: Mini-reviewmentioning
confidence: 99%
“…17 Severe combined immunodeficiency (SCID) mice were first injected with Daudi B-cells transfected with luciferase, and then treated with either 0.5 mg/kg of ofatumumab or anti-KLH 18; NCT00093314 CLL 300 (Group B) or 500 (Group C) mg doses were administered Remission rate was 50% in high in first of 4 treatment weeks. Concentrations were increased to dosage group.…”
Section: Clinical Studies In Chronic Lymphocytic Leukemiamentioning
confidence: 99%
“…Daudi-luc cells and UM-9-luc cells were generated as described previously (19)(20)(21). Ramos cells were provided by Prof. J. Golab (Department of Immunology, Center of Biostructure Research, The Medical University of Warsaw, Warsaw, Poland).…”
Section: Cellsmentioning
confidence: 99%